A Schottky junction photocatalyst, preparation method thereof and application in biomass-based alcohol oxidation

By introducing defects and interface chemical bonds into Schottky junction photocatalysts, a strong built-in electric field is induced, and combined with the joint regulation of the body phase electric field and the interface electric field, a Schottky junction photocatalyst with a 3D flower spherical layered heterostructure was prepared, which solved the problem of low reaction efficiency during the oxidation of biomass-based alcohols and achieved efficient and selective conversion effect.

CN119034777BActive Publication Date: 2025-04-15UNIV OF SCI & TECH OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411261082.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-04-15
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The prior art has low reaction efficiency during the oxidation of biomass-based alcohols and is difficult to achieve high selectivity and activity.

Method used

By introducing defects and interface chemical bonds into Schottky junction photocatalysts, strong built-in electric field, combined regulation of the combined phase electric field and the interface electric field, a Schottky junction photocatalyst with a 3D flower spherical layered heterostructure was prepared.

Benefits of technology

The oxidative conversion efficiency and selectivity of biomass-based alcohols are significantly improved under room temperature conditions, and can efficiently convert biomass-based alcohols into aldehydes/ketones and jointly produce hydrogen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_14
    Figure SMS_14
Patent Text Reader

Abstract

The present invention provides a method for preparing a Schottky junction photocatalyst. Compared with the prior art, the present invention uses hydrazine hydrate to assist the formation of S vacancies and uses NH 4 + In situ self-assembly of preferred CdS and Ti by mixed solvent strategy 3 C 2 CdS / Ti 3 C 2 The Schottky junction nanoreactor accelerates the separation and migration of photogenerated carriers and inhibits the recombination of electron-hole pairs by jointly regulating the bulk electric field and the interface electric field. The full-space electric field of the heterojunction catalyst is strengthened by the combined modulation of the bulk electric field and the interface electric field. Its unique structural advantage greatly increases the specific surface area of ​​the semiconductor and exposes more active sites. The adjacent redox sites are beneficial to the redox catalysis of the substrate, so that the 3D flower ball-shaped layered heterostructure reactor constructed by the present invention can efficiently and highly selectively convert biomass-based alcohols into aldehydes / ketones and jointly produce hydrogen at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a Schottky junction photocatalyst, a preparation method thereof and an application thereof in the oxidation of biomass-based alcohols. Background Art

[0002] The overconsumption of non-renewable fossil energy such as coal, oil and natural gas and the wanton emission of greenhouse gases are the main challenges facing the sustainable development of human society in the 21st century. The "dual carbon" goal is imminent. As a renewable energy with abundant reserves, environmental friendliness and diverse value-added channels, biomass has great development potential for its efficient catalytic conversion into a sustainable production channel for fine chemicals and liquid fuels.

[0003] Photocatalysis is indirectly triggered by photoexcited electron holes, bringing hope for biomass value-added conversion under room temperature conditions. However, biomass platform molecules have poor reaction efficiency due to diverse reaction pathways, complex reaction networks, and uncontrollable reaction processes. Therefore, it is crucial to synthesize powerful multifunctional catalysts to target and control biomass value-added conversion, especially in the system of biomass alcohol value-added conversion into aldehydes / ketones. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a Schottky junction photocatalyst with a strong built-in electric field induced by defects and interface chemical bonds, a preparation method thereof and application in biomass-based alcohol oxidation.

[0005] The present invention provides a method for preparing a Schottky junction photocatalyst, comprising the following steps:

[0006] S1) heating the CdS nano-flower balls and hydrazine hydrate in the first mixed solution to obtain sulfur-deficient CdS;

[0007] S2) In a protective atmosphere, the sulfur defect CdS, Ti 3 C 2 The nanoparticles and the ammonium salt are mixed in a second mixed solution, and then allowed to stand under low temperature conditions to obtain an intermediate product;

[0008] S3) annealing the intermediate product to obtain a Schottky junction photocatalyst;

[0009] The first mixed solution and the second mixed solution are independently a polyamine solvent and an alcohol solvent.

[0010] Preferably, the CdS nano flower ball is prepared according to the following method:

[0011] Mixing the cadmium source and the sulfur source in a third mixed solution, heating and performing a solvothermal reaction, to obtain CdS nano flower balls;

[0012] The third mixed solution is a polyamine solvent and an alcohol solvent;

[0013] And / or, the Ti 3 C 2 The nanoparticles were prepared according to the following method:

[0014] A1) Ti 3 C 2 Al is heated and etched in a hydrochloric acid and lithium fluoride system to obtain accordion-shaped multilayer MXene;

[0015] A2) The accordion-shaped multilayer MXene was subjected to ice bath ultrasound in water to obtain Ti 3 C 2 Nanoparticles.

[0016] Preferably, the cadmium source is selected from cadmium acetate;

[0017] And / or, the sulfur source is selected from thiourea;

[0018] And / or, the molar ratio of the cadmium source to the sulfur source is 1:(2-10);

[0019] And / or, the mixing time is 4 to 8 hours;

[0020] And / or, the temperature of the solvent thermal reaction is 80°C to 100°C;

[0021] And / or, the solvent thermal reaction time is 30 to 60 h;

[0022] And / or, after the solvothermal reaction is completed, centrifugation, washing and vacuum drying are performed to obtain CdS nano flower balls;

[0023] And / or, the concentration of hydrochloric acid in the hydrochloric acid and lithium fluoride system is 5 to 15 mol / L;

[0024] and / or, the concentration of lithium fluoride in the hydrochloric acid and lithium fluoride system is 0.05-0.2 g / mL;

[0025] And / or, the Ti 3 C 2 The ratio of Al to hydrochloric acid and lithium fluoride system is 1 g: (5~15) mL;

[0026] And / or, the etching temperature is 60° C. to 100° C.;

[0027] And / or, the etching time is 15 to 30 hours.

[0028] Preferably, the volume ratio of the polyamine solvent to the alcohol solvent in the first mixed solution, the second mixed solution and the third mixed solution is independently (3-1):1;

[0029] And / or, the polyamine solvent is selected from diethylenetriamine;

[0030] And / or, the alcohol solvent is selected from ethanol.

[0031] Preferably, in step S1), the ratio of the CdS nano flower ball to hydrazine hydrate is (10-30) mg: 1 mL;

[0032] And / or, the ratio of the CdS nano flower ball to the first mixed solution is (1-10) mg: 1 mL;

[0033] And / or, the temperature of the heating treatment is 180°C to 300°C;

[0034] And / or, the heating treatment time is 1 to 10 h.

[0035] Preferably, the step S1) is specifically as follows: dispersing the CdS nano-flower balls in the first mixed solution, then adding hydrazine hydrate and stirring, and then heating to obtain sulfur-deficient CdS; the dispersion time is 0.5-2 h; and the stirring time is 1-3 h.

[0036] Preferably, the Ti 3 C 2 The mass of the nanoparticles is sulfur-deficient CdS and Ti 3 C 2 1%~20% of the total mass of nanoparticles;

[0037] And / or, the ammonium salt is selected from NH 4 HCO 3 ;

[0038] and / or, the ratio of the ammonium salt to the sulfur-deficient CdS is (0.01-0.1) mol: 1 g;

[0039] And / or, the mixing method in step S2) is ultrasound; the mixing temperature is 0°C to 10°C;

[0040] And / or, the standing temperature is 0°C to 10°C; the standing time is 30 to 90 min;

[0041] And / or, the annealing temperature is 150° C. to 200° C.; the annealing time is 2 to 10 h.

[0042] The present invention also provides a Schottky junction photocatalyst prepared by the above preparation method.

[0043] Preferably, the Schottky junction photocatalyst has a 3D flower-ball-shaped layered heterostructure.

[0044] The present invention also provides a method for biomass-based alcohol oxidation, comprising the following steps:

[0045] The above-mentioned Schottky junction photocatalyst is used as a catalyst to photocatalyze the biomass-derived alcohol into aldehyde and ketone compounds.

[0046] The invention provides a method for preparing a Schottky junction photocatalyst, comprising the following steps: S1) heating CdS nano flower balls and hydrazine hydrate in a first mixed solution to obtain sulfur-deficient CdS; S2) mixing the sulfur-deficient CdS, Ti 3 C 2 The nanoparticles and the ammonium salt are mixed in a second mixed solution, and then allowed to stand at low temperature to obtain an intermediate product; S3) the intermediate product is annealed to obtain a Schottky junction photocatalyst; the first mixed solution and the second mixed solution are independently a polyamine solvent and an alcohol solvent. Compared with the prior art, the present invention uses hydrazine hydrate to assist the formation of S vacancies, and uses NH 4 + In situ self-assembly of preferred CdS and Ti by mixed solvent strategy 3 C 2 CdS / Ti 3 C 2 The Schottky junction nanoreactor accelerates the separation and migration of photogenerated carriers and inhibits the recombination of electron-hole pairs by jointly regulating the bulk electric field and the interface electric field. The combined modulation of the bulk electric field and the interface electric field strengthens the full-space electric field of the heterojunction catalyst. Its unique structural advantage greatly increases the specific surface area of ​​the semiconductor and exposes more active sites. The adjacent redox sites are beneficial to the redox catalysis of the substrate, so that the 3D flower ball-shaped layered heterostructure reactor constructed by the present invention can efficiently and highly selectively convert biomass-based alcohols into aldehydes / ketones and jointly produce hydrogen at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The Schottky junction photocatalyst Sv-CdS / Ti obtained in Example 1 of the present invention 3 C 2 -2 scanning electron microscope and transmission electron microscope images;

[0048] Figure 2 The Schottky junction photocatalyst Sv-CdS / Ti obtained in Example 1 of the present invention 3 C 2 -2 Result diagram of catalytic oxidation of different biomass-based alcohols. DETAILED DESCRIPTION

[0049] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The invention provides a method for preparing a Schottky junction photocatalyst, comprising the following steps: S1) heating CdS nano flower balls and hydrazine hydrate in a first mixed solution to obtain sulfur-deficient CdS; S2) mixing the sulfur-deficient CdS, Ti 3 C 2 The nanoparticles and the ammonium salt are mixed in a second mixed solution, and then allowed to stand at low temperature to obtain an intermediate product; S3) the intermediate product is annealed to obtain a Schottky junction photocatalyst; the first mixed solution and the second mixed solution are independently a polyamine solvent and an alcohol solvent.

[0051] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.

[0052] In the present invention, the CdS nano flower ball is preferably prepared according to the following method: a cadmium source and a sulfur source are mixed in a third mixed solution, and heated to perform a solvothermal reaction to obtain a CdS nano flower ball; the cadmium source can be a cadmium source well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably cadmium acetate; the sulfur source can be a sulfur source well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably thiourea; the molar ratio of the cadmium source to the sulfur source is preferably 1: (2-10), more preferably 1: (4-8), more preferably 1: (4-6), and most preferably 1: 5; the third mixed solution is a polyamine solvent and an alcohol solvent; the volume ratio of the polyamine solvent to the alcohol solvent is preferably (3-1): 1, more preferably (2.5-1.5): 1, and more preferably 2: 1; the polyamine solvent is preferably diethylenetriamine; the alcohol solvent is preferably ethanol; the ratio of the cadmium source to the third mixed solution is 1 mmol: (20-30) mL, more preferably 1 mmol: 25 mL; the mixing method is preferably stirring; the mixing time is preferably 4-8 h, more preferably 5-7 h, and more preferably 6 h; the solvothermal reaction is preferably carried out in an autoclave, more preferably in a polytetrafluoroethylene-lined autoclave; the temperature of the solvothermal reaction is preferably 80°C-100°C; the time of the solvothermal reaction is preferably 30-60 h, more preferably 35-55 h, more preferably 40-50 h, more preferably 45-50 h, and most preferably 48 h; after the solvothermal reaction, it is preferably centrifuged, washed and vacuum dried to obtain CdS nano flower balls; the washing is preferably carried out using ethanol and deionized water; the temperature of the vacuum drying is preferably 50°C-70°C, more preferably 55°C-65°C, and more preferably 60°C.

[0053] In the present invention, the Ti 3 C 2 The nanoparticles are preferably prepared by chemical etching combined with ice bath ultrasonic centrifugation to separate the parent Ti 3 C 2 Al stripping to Ti 3 C 2 The nanoparticles are preferably prepared by the following method: A1) Ti 3 C 2 Al is heated in a hydrochloric acid and lithium fluoride system for etching to obtain an accordion-shaped multilayer MXene; A2) the accordion-shaped multilayer MXene is subjected to ice bath ultrasound in water to obtain Ti 3 C 2Nanoparticles; the concentration of hydrochloric acid in the hydrochloric acid and lithium fluoride system is preferably 5-15 mol / L, more preferably 6-12 mol / L, more preferably 8-10 mol / L, and most preferably 9 mol / L; the concentration of lithium fluoride in the hydrochloric acid and lithium fluoride system is 0.05-0.2 g / mL, more preferably 0.1-0.2 g / mL, and more preferably 0.15-0.2 g / mL; the Ti 3 C 2 The ratio of Al to hydrochloric acid and lithium fluoride system is preferably 1 g: (5-15) mL, more preferably 1 g: (8-12) mL, and more preferably 1 g: 10 mL; the etching is preferably carried out under stirring; the etching temperature is preferably 60°C-100°C, more preferably 70°C-90°C, more preferably 75°C-85°C, and most preferably 80°C; the etching time is preferably 15-30 h, more preferably 18-28 h, more preferably 20-26 h, more preferably 22-26 h, and most preferably 24 h; after the etching is completed, it is preferably centrifuged, washed, and dried to obtain an accordion-shaped multilayer MXene; the washing is preferably carried out with deionized water; the drying is preferably vacuum drying; the drying temperature is preferably 50°C-70°C, more preferably 55°C-65°C, and more preferably 60°C; the drying time is preferably 6-12 h, more preferably 8-12 h; the mass ratio of the accordion-shaped multilayer MXene to water is preferably (5-15):1, more preferably (8-12):1, and more preferably 10:1; the water is preferably deionized water; the power of the ice bath ultrasound is preferably 200-300 W, more preferably 250 W; the time of the ice bath ultrasound is preferably 1-5 h, more preferably 2-4 h, and more preferably 3 h; after the ice bath ultrasound, the supernatant obtained is Ti 3 C 2 Homogeneous dispersion of nanoparticles.

[0054] The CdS nano flower balls and hydrazine hydrate are heated in the first mixed solution to obtain sulfur-deficient CdS; the ratio of the CdS nano flower balls to hydrazine hydrate is preferably (10-30) mg:1 mL, more preferably (15-25) mg:1 mL, more preferably (18-22) mg:1 mL, and most preferably 20 mg:1 mL; the first mixed solution is a polyamine solvent and an alcohol solvent; the volume ratio of the polyamine solvent to the alcohol solvent is preferably (3-1):1, more preferably (2.5-1.5):1, and more preferably 2:1; the polyamine solvent is preferably diethylenetriamine; the alcohol solvent is preferably ethanol; in the present invention, this step is specifically: dispersing the CdS nano flower balls in the first mixed solution, then adding hydrazine hydrate and stirring, and then heating to obtain sulfur-deficient CdS; the dispersion time is preferably 0.5-2 h, more preferably 0.8-1.5 h, and more preferably 1 h; the stirring time is preferably 1-3 h, more preferably 1.5-2.5 h, more preferably 1.8~2.2 h, most preferably 2 h; the heating treatment is preferably carried out in an autoclave, more preferably in a stainless steel autoclave; the heating treatment temperature is preferably 180℃~300℃, more preferably 200℃~280℃, more preferably 220℃~260℃, most preferably 240℃; the heating treatment time is preferably 1~10 h, more preferably 3~8 h, more preferably 4~6 h, most preferably 5 h; after the heating treatment is completed, it is preferably centrifuged, washed and freeze-dried to obtain sulfur-deficient CdS; the washing is preferably carried out with ethanol and deionized water; the freeze-drying temperature is preferably -40℃~-20℃, more preferably -30℃; the freeze-drying vacuum is preferably 5~15 Pa, more preferably 5~10 Pa, and more preferably 8 Pa.

[0055] In a protective atmosphere, the sulfur defect CdS, Ti 3 C 2 The nanoparticles and the ammonium salt are mixed in a second mixed solution, and then allowed to stand at low temperature to obtain an intermediate product; the protective atmosphere can be any protective atmosphere known to those skilled in the art, and there is no particular limitation, and argon is preferred in the present invention; the Ti 3 C 2 The quality of the nanoparticles is preferably sulfur-deficient CdS and Ti 3 C 2 1% to 20% of the total mass of the nanoparticles, more preferably 2% to 18%, more preferably 4% to 16%, more preferably 4% to 12%, more preferably 8% to 12%, and most preferably 8%; in some embodiments provided by the present invention, the Ti 3 C 2 The mass of the nanoparticles is specifically sulfur-deficient CdS and Ti 3C 2 4%, 8%, 12% or 16% of the total mass of the nanoparticles; the ammonium salt is any ammonium salt known to those skilled in the art, and there is no particular limitation. In the present invention, NH 4 HCO 3 one or more; the ratio of the ammonium salt to the sulfur-deficient CdS is preferably (0.01-0.1) mol: 1 g, more preferably (0.03-0.08) mol: 1 g, more preferably (0.04-0.06) mol: 1 g, and most preferably 0.05 mol: 1 g; the second mixed solution is a polyamine solvent and an alcohol solvent; the volume ratio of the polyamine solvent to the alcohol solvent is preferably (3-1): 1, more preferably (2.5-1.5): 1, and more preferably 2: 1; the polyamine solvent is preferably diethylenetriamine; the alcohol solvent is preferably ethanol; the mixing method is preferably ultrasound; the mixing temperature is preferably 0°C-10°C, more preferably 2°C-8°C, more preferably 4°C-6°C, and most preferably 5°C; the mixing time is preferably 10-30 min, more preferably 10-25 min, and more preferably 15-20 min; in the present invention, the step is specifically: in a protective atmosphere, sulfur-deficient CdS and Ti 3 C 2 The nanoparticles are subjected to a first ultrasonic mixing in the second mixed solution, ammonium salt is added, and a second ultrasonic mixing is performed, and then the mixture is allowed to stand at low temperature to obtain an intermediate product; the temperatures of the first ultrasonic mixing and the second ultrasonic mixing are each independently 0°C to 10°C, more preferably 2°C to 8°C, more preferably 4°C to 6°C, and most preferably 5°C; the powers of the first ultrasonic mixing and the second ultrasonic mixing are each independently preferably 200 to 300 W, more preferably 250 W; the time of the first ultrasonic mixing is preferably 1 to 10 min, more preferably 2 to 8 min, more preferably 4 to 6 min, and most preferably 5 min; the time of the second ultrasonic mixing is preferably 5 to 20 min, more preferably 5 to 15 min, more preferably 8 to 12 min, and most preferably 10 min; the temperature of the standing is preferably 0 to 10°C, more preferably 2 to 8°C, more preferably 4 to 6°C, and most preferably 5°C; the standing time is preferably 30 to 90 min, more preferably 40 to 80 min, more preferably 50 to 70 min, and most preferably 60 min; a flocculent precipitate may be formed by standing and settle to the bottom, and after separating the supernatant, the flocculent precipitate may be preferably subjected to vacuum freeze drying to obtain an intermediate; the freeze drying temperature is preferably -40°C to -20°C, more preferably -30°C; the vacuum degree of the freeze drying is preferably 5 to 15 Pa, more preferably 5 to 10 Pa, and further preferably 8 Pa.

[0056] The intermediate product is annealed to obtain a Schottky junction photocatalyst; the annealing is preferably carried out in a protective atmosphere; the protective atmosphere is preferably argon; the annealing temperature is preferably 150°C to 200°C, more preferably 170°C to 190°C, and more preferably 180°C; the annealing time is preferably 2 to 10 h, more preferably 4 to 8 h, and more preferably 6 h.

[0057] The present invention uses hydrazine hydrate to assist the formation of S vacancies and uses NH 4 + In situ self-assembly of preferred CdS and Ti by mixed solvent strategy 3 C 2 CdS / Ti 3 C 2 The Schottky junction nanoreactor accelerates the separation and migration of photogenerated carriers and inhibits the recombination of electron-hole pairs by jointly regulating the bulk electric field and the interface electric field. The combined modulation of the bulk electric field and the interface electric field strengthens the full-space electric field of the heterojunction catalyst. Its unique structural advantage greatly increases the specific surface area of ​​the semiconductor and exposes more active sites. The adjacent redox sites are beneficial to the redox catalysis of the substrate, so that the 3D flower ball-shaped layered heterostructure reactor constructed by the present invention can efficiently and highly selectively convert biomass-based alcohols into aldehydes / ketones and jointly produce hydrogen at room temperature.

[0058] Furthermore, the preparation method provided by the present invention has a simple process, low requirements on equipment and process, wide application and great prospects.

[0059] The present invention also provides a Schottky junction photocatalyst prepared by the above preparation method.

[0060] According to the present invention, the Schottky junction photocatalyst is preferably formed by bonding CdS nanospheres with sulfur defects and Ti 3 C 2 The nanoparticles are obtained by self-assembly.

[0061] According to the present invention, the Schottky junction photocatalyst has a 3D flower ball-shaped layered heterostructure.

[0062] The present invention also provides a method for oxidizing biomass-based alcohols, comprising the following steps: using the above-mentioned Schottky junction photocatalyst as a catalyst, photocatalytically converting biomass-derived alcohols into aldehyde and ketone compounds.

[0063] Specifically, the biomass-derived alcohol is converted into aldehyde and ketone compounds under room temperature conditions.

[0064] Specifically, the biomass-derived alcohol preferably has a structure shown in formula (I):

[0065] Formula (I);

[0066] Wherein, A is an aryl group or a heterocyclic group, more preferably a phenyl group or a furyl group; 1 is H, substituted or unsubstituted C1-C10 alkyl, C1-C10 aldehyde, C1-C10 ketone, C2-C10 ester, C1-C10 alkoxy or halogen, preferably H, substituted or unsubstituted C1-C5 alkyl, C1-C5 aldehyde, C1-C5 ketone, C2-C6 ester, C1-C5 alkoxy or halogen, more preferably H, substituted or unsubstituted C1-C3 alkyl, C1-C3 aldehyde, C1-C3 The ketone group of C2~C4, the ester group of C1~C3, the alkoxy group of C1~C3 or the halogen, and preferably H, substituted or unsubstituted C1~C2 alkyl group, C1~C2 aldehyde group, C1~C2 ketone group, C2~C3 ester group, C1~C2 alkoxy group or halogen; the substituent of the substituted C1~C10 alkyl group is preferably hydroxyl or halogen; the halogen is any halogen known to those skilled in the art without any special limitation, and is preferably F, Cl or Br in the present invention; the R 2 It is H or a C1-C10 alkyl group, preferably H or a C1-C5 alkyl group, more preferably H or a C1-C3 alkyl group, and still more preferably H, methyl or ethyl.

[0067] More specifically, the biomass-derived alcohol is one or more of formula (I-1) to formula (I-12):

[0068] Formula (I-1) Formula (I-2) Formula (I-3)

[0069] Formula (I-4) Formula (I-5) Formula (I-6)

[0070] Formula (I-7) Formula (I-8) Formula (I-9)

[0071] Formula (I-10) Formula (I-11) Formula (I-12)

[0072] Specifically, the photocatalysis is visible light catalysis.

[0073] Specifically, the conversion pressure is preferably 0.5-2 bar, more preferably 0.8-1.5 bar, and even more preferably 1 bar.

[0074] The Schottky junction photocatalyst provided by the present invention uses strong built-in electric field photocatalysis induced by defects and interface chemical bonds, so that the 3D flower ball-shaped layered heterogeneous structure reactor can be used to efficiently and selectively convert biomass-based alcohols into aldehydes / ketones at room temperature, greatly improving the induction of semiconductor photocatalysts on specific catalytic behaviors of substrate molecules, and significantly enhancing the catalytic activity and selectivity. It provides a new idea and method for the photocatalytic value-added conversion of biomass-derived platform molecules.

[0075] In order to further illustrate the present invention, a Schottky junction photocatalyst provided by the present invention, a preparation method thereof and application in biomass-based alcohol oxidation are described in detail below in conjunction with examples.

[0076] The reagents used in the following examples are all commercially available.

[0077] Example

[0078] 1. Synthesis of CdS with different crystal orientations by mixed solvent method:

[0079] Mixed solvent method for synthesizing CdS: 2 mmol of cadmium acetate·dihydrate and 10 mmol of thiourea were added to a mixed solution of diethylenetriamine and ethanol (V DETA :V EtOH =2:1, 50 mL) and then stirred for 6 hours. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and heated in an oven at 80 °C for 48 hours. The yellow precipitate was collected by centrifugation and washed several times with ethanol and deionized water. Finally, the sample was vacuum dried at 60 °C for 12 hours to obtain CdS nanoflower balls.

[0080] 2. Preparation of defective CdS (Sv-CdS):

[0081] Sv-CdS is a N 2 H 4 ·H 2 O-assisted mixed solvothermal strategy. Specifically, 200 mg CdS was dispersed in 40 mL mixed solution (V DETA :V EtOH =2:1) ​​for 1 hour. Then, 10 ml of N 2 H 4 ·H 2 O and stirred for 2 h. Afterwards, the mixture was transferred to a 100 mL stainless steel autoclave and kept in an oven at 240 °C for 5 h. Finally, the precipitate was separated by centrifugation and washed several times with ethanol and deionized water, and then freeze-dried (temperature -30 °C, vacuum 8 Pa) for 72 h to obtain a yellow powder labeled Sv-CdS.

[0082] 3. Stripping of MAX phase:

[0083] 2 g Ti 3 C 2 The Al powder was slowly added to a mixed solution of hydrochloric acid (20 mL, 9 M) and lithium fluoride (2 g) and stirred at 80 °C for 24 h to selectively remove Ti. 3 C 2 Al layer in the middle of Al and obtain accordion-like multilayer MXene (Ti 3 C 2 T X The product was then centrifuged, washed with deionized water, and dried overnight in vacuum at 60 °C. 3 C 2 T X Add to 10 mg of deionized water, ultrasonicate in an ice bath at 250 W for 3 hours, and the supernatant is Ti 3 C 2 Homogeneous dispersion of nanoparticles (2 mg / mL).

[0084] 4. Sv-CdS / Ti 3 C 2 Synthesis of heterostructures:

[0085] First, different amounts of Ti 3 C 2 (Specific ratios are shown in Table 1) were added to the prepared Sv-CdS solution (200 mg Sv-CdS dispersed in 40 mL mixed solution V DETA :V EtOH =2:1) ​​and ultrasonically treated at 5 °C and 250 W for 5 min under argon atmosphere. Then, 10 mL 1 mol / L NH 4 HCO 3 The solution was gradually added to the above mixed solution and ultrasonically treated at 250 W for 10 minutes under an argon atmosphere. After standing at 5°C for 1 hour, a flocculent precipitate was formed and settled to the bottom of the beaker. After separating the supernatant, the flocculent precipitate was freeze-dried at -30°C and 8 Pa for 72 h to obtain Sv-CdS / Ti 3 C 2 powder. Finally, Sv-CdS / Ti 3 C 2 The powder was annealed at 180 °C for 6 h in a tube furnace under an argon atmosphere to obtain a Schottky junction photocatalyst denoted as Sv-CdS / Ti 3 C 2 -1~Sv-CdS / Ti 3 C 2 -4.

[0086] Scanning electron microscopy and transmission electron microscopy were used to characterize the Schottky junction photocatalyst Sv-CdS / Ti 3 C 2 -2 was analyzed and the scanning electron microscope and transmission electron microscope images were obtained as shown in Figure 1 As shown, a is a scanning electron microscope image and b is a transmission electron microscope image.

[0087] Photocatalytic conversion of biomass-based alcohols For example: Photoredox reaction experiments were conducted in sealed glass containers at room temperature. The visible light source was a top-irradiated 300 W xenon lamp equipped with a UV cutoff filter (λ ≥ 420 nm). Typically, 10 mg of Schottky junction photocatalyst was suspended in 10 mL of 10 mM 5-hydroxymethylfurfural (HMF) aqueous solution. Before the reaction, the suspension was purged with argon for 30 minutes to achieve an oxygen-free environment, and the visible light-driven photocatalytic reaction was carried out at room temperature under 1 bar argon pressure. The concentrations of liquid reactants and products were analyzed by high-performance liquid chromatography (HPLC, Shimadzu LC-20AD), and the hydrogen content was analyzed by gas chromatograph (Agilent GC-7890A, thermal conductivity detector (TCD), argon as carrier gas), and the results are shown in Table 1.

[0088] According to the above conditions, different substrates are changed and the results are as follows Figure 2 shown.

[0089] Table 1 Effect of different catalysts on the photocatalytic preparation of 2,5-diformylfuran from 5-hydroxymethylfurfural

[0090]

[0091] Table 1 shows that the 3D layered flower ball CdS / Ti 3 C 2 Schottky junction photocatalysis has a good effect on biomass aldehyde production.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Schottky junction photocatalyst, characterized in that: The following steps are involved: S1) heating the CdS nano flower balls and hydrazine hydrate in the first mixed solution to obtain sulfur-deficient CdS; S2) in a protective atmosphere, mixing the sulfur-deficient CdS, Ti3C2 nanoparticles and ammonium salt in a second mixed solution, and then standing at low temperature to obtain an intermediate product; the mass of the Ti3C2 nanoparticles is 8% to 12% of the total mass of the sulfur-deficient CdS and the Ti3C2 nanoparticles; the ratio of the ammonium salt to the sulfur-deficient CdS is (0.01 to 0.1) mol: 1g; the standing temperature is 0°C to 10°C; and the standing time is 30 to 90 min; S3) annealing the intermediate product to obtain a Schottky junction photocatalyst; the annealing temperature is 150° C. to 200° C.; the annealing time is 2 to 10 hours; The first mixed solution and the second mixed solution are independently a polyamine solvent and an alcohol solvent.

2. The preparation method according to claim 1, characterized in that: The CdS nano flower ball is prepared according to the following method: Mixing the cadmium source and the sulfur source in a third mixed solution, heating and performing a solvothermal reaction, to obtain CdS nano flower balls; The third mixed solution is a polyamine solvent and an alcohol solvent; And / or, the Ti3C2 nanoparticles are prepared according to the following method: A1) heating Ti3C2Al in a hydrochloric acid and lithium fluoride system for etching to obtain an accordion-shaped multilayer MXene; A2) The accordion-shaped multilayer MXene was subjected to ice bath sonication in water to obtain Ti3C2 nanoparticles.

3. The preparation method according to claim 2, characterized in that: The cadmium source is selected from cadmium acetate; And / or, the sulfur source is selected from thiourea; And / or, the molar ratio of the cadmium source to the sulfur source is 1:(2-10); And / or, the mixing time is 4 to 8 hours; and / or, the temperature of the solvent thermal reaction is 80° C. to 100° C.; And / or, the solvent thermal reaction time is 30 to 60 hours; And / or, after the solvothermal reaction is completed, centrifugation, washing and vacuum drying are performed to obtain CdS nano flower balls; and / or, the concentration of hydrochloric acid in the hydrochloric acid and lithium fluoride system is 5 to 15 mol / L; and / or, the concentration of lithium fluoride in the hydrochloric acid and lithium fluoride system is 0.05 to 0.2 g / mL; and / or, the ratio of the Ti3C2Al to the hydrochloric acid and lithium fluoride system is 1 g: (5-15) mL; And / or, the etching temperature is 60° C. to 100° C.; And / or, the etching time is 15 to 30 hours.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The volume ratio of the polyamine solvent to the alcohol solvent in the first mixed solution, the second mixed solution and the third mixed solution is independently (3-1):1; And / or, the polyamine solvent is selected from diethylenetriamine; And / or, the alcohol solvent is selected from ethanol.

5. The preparation method according to claim 1, characterized in that: In the step S1), the ratio of the CdS nano flower ball to hydrazine hydrate is (10-30) mg: 1 mL; And / or, the ratio of the CdS nano flower ball to the first mixed solution is (1-10) mg: 1 mL; And / or, the temperature of the heating treatment is 180°C to 300°C; And / or, the heating treatment time is 1 to 10 hours.

6. The preparation method according to claim 1, characterized in that: The step S1) is specifically as follows: dispersing the CdS nano-flower balls in the first mixed solution, then adding hydrazine hydrate and stirring, and then heating to obtain sulfur-deficient CdS; the dispersion time is 0.5 to 2 hours; and the stirring time is 1 to 3 hours.

7. The preparation method according to claim 1, characterized in that: The ammonium salt is selected from NH4HCO3; And / or, the mixing method in step S2) is ultrasound; the mixing temperature is 0°C to 10°C.

8. A Schottky junction photocatalyst prepared by the preparation method according to any one of claims 1 to 7.

9. The Schottky junction photocatalyst according to claim 8, characterized in that: The Schottky junction photocatalyst has a 3D flower ball-shaped layered heterostructure.

10. A method for biomass-based alcohol oxidation, characterized in that: The following steps are involved: Biomass-derived alcohols are photocatalytically converted into aldehydes and ketones using the Schottky junction photocatalyst prepared by the preparation method of any one of claims 1 to 7 or the Schottky junction photocatalyst of claim 8 or 9 as a catalyst.

Citation Information

Patent Citations

  • Method for preparing 2,5-furandicarboxaldehyde through photocatalytic dehydrogenation of 5-hydroxymethylfurfural

    CN113387911A